2015
DOI: 10.1007/s00345-015-1669-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a role for computed tomography and bone scintigraphy in prostate cancer staging? An analysis from the EUREKA-1 database

Abstract: preoperative risk factors excluded any additional predictive ability of CT even in the high-risk group (P 0.40). These data are confirmed by ROC curve analysis, showing a low AUC of 54 % for CT, compared with 69 % for Partin tables and 80 % for Briganti nomogram. BS showed some positivity in 74 cases, only four of whom progressed, while 49 patients with negative BS progressed during their followup, six of them immediately after surgery. Conclusions According to our opinion, the role of CT and BS should be rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
(8 reference statements)
2
25
0
4
Order By: Relevance
“…As for implementation of BS, several studies have suggested that the use of BS should be restricted to high-risk patients since both sensitivity and specificity of BS are relatively low and BS can only provide limited assistance to evaluate PCa in the pre-treatment stage [47,48]. Consistently, our study demonstrated that BS was less capable in sensitive detection of metastatic lesions in spine, pelvis and skull in comparison to MRI (Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…As for implementation of BS, several studies have suggested that the use of BS should be restricted to high-risk patients since both sensitivity and specificity of BS are relatively low and BS can only provide limited assistance to evaluate PCa in the pre-treatment stage [47,48]. Consistently, our study demonstrated that BS was less capable in sensitive detection of metastatic lesions in spine, pelvis and skull in comparison to MRI (Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…found the sensitivity for CT scans of 42% and specificity of 82% . The poor performance of CT for the detection of nodal metastases has been confirmed in other recent studies …”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…CT is often used in the initial staging of advanced disease to follow nodal involvement and bone metastasis, and is especially useful in excluding extensive osseous metastasis or evaluating pathologic fractures. Although nodal metastasis on CT is specific, there is low sensitivity [100]. …”
Section: Prostate Adenocarcinomamentioning
confidence: 99%